2011
DOI: 10.5194/hess-15-2979-2011
|View full text |Cite
|
Sign up to set email alerts
|

Discharge estimation combining flow routing and occasional measurements of velocity

Abstract: Abstract.A new procedure is proposed for estimating river discharge hydrographs during flood events, using only water level data at a single gauged site, as well as 1-D shallow water modelling and occasional maximum surface flow velocity measurements. One-dimensional diffusive hydraulic model is used for routing the recorded stage hydrograph in the channel reach considering zero-diffusion downstream boundary condition. Based on synthetic tests concerning a broad prismatic channel, the "suitable" reach length i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
0
26
0
3
Order By: Relevance
“…Finally, as shown by some authors [9,23], the availability of "non-contact" radar sensors for velocity measurements could, on the one hand, have the considerable advantage of rapid discharge monitoring allowing the measurement in different river sites for the same flood event if hand-held devices are used and, on the other hand, improve the safety conditions for operators..…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as shown by some authors [9,23], the availability of "non-contact" radar sensors for velocity measurements could, on the one hand, have the considerable advantage of rapid discharge monitoring allowing the measurement in different river sites for the same flood event if hand-held devices are used and, on the other hand, improve the safety conditions for operators..…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, many authors, e.g. [8,9,23,24], explored the possibility of exploiting water surface velocity observations to estimate discharge. The theoretical basis of discharge estimation using surface flow velocity can be traced back to the entropic model proposed by Chiu [4] who established a bridge between the probability domain, wherein a probability distribution of the velocity is surmised, and the physical space by deriving the cumulative probability distribution function in terms of curvilinear coordinates in the physical space.…”
Section: Entropy Methodsmentioning
confidence: 99%
“…Equation (6) thus has validity on the y-axis, but different authors [25][26][27][28] have shown that it is reasonable in practical applications to extend this profile to the generic vertical of a cross-section without having to rely on Equation (5) for the assigned z.…”
Section: The Entropy Methodsmentioning
confidence: 99%
“…The actual value of this ratio can be deduced on the basis of a series of observations relating to a number of events and a number of verticals [26]. …”
Section: Methodsmentioning
confidence: 99%
“…O primeiro tipo são os modelos que usam medidas de velocidades ou vazões. Eles requerem menos informações de batimetria, mas necessitam de informações de vazões e da seção para ajustar os parâmetros do modelo (CORATO et al, 2011;MORAMARCO et al, 2011). Informações de velocidades podem ser empregadas para este fim, mas deve-se considerar um perfil de velocidades para estimar a vazão (CHOO et al, 2013(CHOO et al, , 2014.…”
Section: Introductionunclassified